Treatment of diabetic foot ulcers - Rosiński, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
Proper, effective treatment of the syndrome of diabetic foot prolongs life and improves its quality. To assure effectiveness of treatment prompt differential diagnostics between vascular and neuropathic foot is mandatory. In the case of neuropathic foot the main problem is treatment of infected wound. After establishing sensitivity of the pathogen(s) (by culture and antibiogram) we choose antibiotics. The next step in therapy is selection of the right way and time of application of the chosen antibiotic. Besides antibiotic therapy crucial is podiatric processing of the wound and application of different types of dressings which markedly shorten time of treatment.